Methane emission and metabolic heat production of Nellore cattle - De Melo Costa, Cíntia Carol [UNESP]; Maia, Alex Sandro Campos [UNESP]; Berchielli, Telma Teresinha [UNESP]; Nascimento, Sheila Tavares; Nascimento, Carolina Cardoso Nagib [UNESP] (American Society of Agricultural and Biological Engineers (ASABE), 2016)
The aim of this study was to evaluate the methane emission (eCH4, g h-1) of Nellore cattle and to study the relationship with metabolic heat production (q″met, W m-2) and meteorological conditions. The study was conducted in the Animal Biometeorology Laboratory of the São Paulo State University, Jaboticabal, Brazil. Five Nellore cattle with an average live weight of 750 kg and similar age and body condition were evaluated. A Latin square experimental design was used (5classes of hours (8-10h; 10-12h; 12-14h; 14-16h; 16-18 h) × 5 days), that was replicated four times, totaling 20 days of data collection. The CH4 emission (eCH4, g h-1) and the metabolic heat production (q″met, W m-2) were measured using an indirect calorimetry system with a facial mask adjusted on the animals' muzzle. The air temperature (TA, °C) and humidity (RH, %) were measured in one second intervals and the solar radiation (GS, W m-2) were measured in intervals of ten minutes. During the observations the means of TA, RH and GS were 30.15±0.02 °C, 60.91±0.09% and 530.73±2.71 W m-2 respectively. Between 8 am and 12:00 pm, Nellore cattle emitted more (P<0.05) methane with a mean of 3.52±0.03 g h-1 the higher value was observed at 10 am (5.72±0.09 g h-1) and the lower value was measured at 17 pm (2.19±0.09 g h-1). The mean of q″met was 146.66±0.49 W m-2 his variable was not influenced by TA (P>0.05). The eCH4 had positive and high correlations with RH, q″met and GS (0.5042, 0.3571 and 0.1455, respectively) and a negative correlation with TA (-0.4401).
Keywords: Beef cattle; Greenhouse gas; Indirect calorimetry; Metabolic heat production